THE CRITICAL THINKING SKILLS OF BIOLOGY PROSPECTIVE TEACHERS IN ECOLOGICAL PRACTICUM - Hunaepi, Hunaepi; Susantini, Endang; Firdaus, Laras; Samsuri, Taufik; Raharjo, Raharjo (Jurnal Ilmiah IKIP Mataram, 2019)
This study aims to identify biology prospective teachersâ€™ critical thinking skills in ecological practicum at IKIP Mataram. The survey method was carried out in this study involving 100 student determined using purposive sampling technique. An essay-shaped test instrument consisting of 6 items developed by the researcher and validated by experts was used to obtain data on biology prospective teachersâ€™ critical thinking skills. The results showed the percentage of basic clarification indikators reached 40%, basic grouping 40%, conclusion 37%, further clarification, 36%, and strategy and tactics 20%. Each of these catalysts showed â‰¥ 40% achievement. These results indicate that students’ critical thinking skills are still in the low category so that serious handling is important to do.